Mutation of the iron‐sulfur cluster assembly gene IBA57 causes fatal infantile leukodystrophy. Issue 6 (14th May 2015) - Debray, François‐Guillaume; Stümpfig, Claudia; Vanlander, Arnaud V.; Dideberg, Vinciane; Josse, Claire; Caberg, Jean‐Hubert; Boemer, François; Bours, Vincent; Stevens, René; Seneca, Sara; Smet, Joél; Lill, Roland; et al.
Abstract: Leukodystrophies are a heterogeneous group of severe genetic neurodegenerative disorders. A multiple mitochondrial dysfunctions syndrome was found in an infant presenting with a progressive leukoencephalopathy. Homozygosity mapping, whole exome sequencing, and functional studies were used to define the underlying molecular defect. Respiratory chain studies in skeletal muscle isolated from the proband revealed a combined deficiency of complexes I and II. In addition, western blotting indicated lack of protein lipoylation. The combination of these findings was suggestive for a defect in the iron‐sulfur (Fe/S) protein assembly pathway. SNP array identified loss of heterozygosity in large chromosomal regions, covering the NFU1 and BOLA3, and the IBA57 and ABCB10 candidate genes, in 2p15‐p11.2 and 1q31.1‐q42.13, respectively. A homozygous c.436C > T (p.Arg146Trp) variant was detected in IBA57 using whole exome sequencing. Complementation studies in a HeLa cell line depleted for IBA57 showed that the mutant protein with the semi‐conservative amino acid exchange was unable to restore the biochemical phenotype indicating a loss‐of‐function mutation of IBA57. In conclusion, defects in the Fe/S protein assembly gene IBA57 can cause autosomal recessive neurodegeneration associated with progressive leukodystrophy and fatal outcome at young age. In the affected patient, the biochemical phenotype was characterized by a defect in the respiratory chain complexes I and II and a decrease in mitochondrial protein lipoylation, both resulting from impaired assembly of Fe/S clusters.